The K-W-L (Know-Want-Learned) Strategy for Enhancing Reading Comprehension Skills of 7th Grade Students at SMP Negeri 1 Tanjung Harapan - Firkas Ali Marpaung (Edelweiss : Journal Of Innovation In Educational Research, 2024)
This study aims to assess the effectiveness of the K-W-L (Know-Want-Learned) strategy in enhancing the reading comprehension skills of 7th-grade students at MTS Negeri 1 Tanjung Harapan during the 2022/2023 academic year. Reading comprehension is a crucial skill that underpins students' academic success across various subjects. The research utilized an experimental approach, involving both a control group and an experimental group. The sample included two 7th-grade classes: one served as the experimental group, which implemented the K-W-L strategy in their learning, while the other functioned as the control group, without using the strategy. Data were gathered through pre- and post-tests measuring reading comprehension and a survey assessing student engagement during the learning process. The findings were analyzed using descriptive statistical methods and hypothesis testing. The results revealed that the K-W-L strategy positively impacted students' reading comprehension abilities. The experimental group exhibited significant improvement in their reading comprehension scores compared to the control group. Additionally, the experimental group showed higher levels of engagement during the learning process, reflecting a positive response to the K-W-L strategy. These outcomes suggest that the K-W-L strategy is an effective approach for improving the reading comprehension skills of 7th-grade students at MTS Negeri 1 Tanjung Harapan. Consequently, it is recommended that educators and teachers consider incorporating this strategy into their teaching practices to support students' academic grow